The Transition of Wittgenstein's Thought and the Potential Influence of Cambridge Economists - Chaparro, Germán Raúl (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this paper is to review the possible influence of John Maynard Keynes, Frank Ramsey, Piero Sraffa and, through the latter, Antonio Gramsci, on the transition of the philosophical thought of Ludwig Wittgenstein. The work reconstructs, from specialized literature, the relationship of the Austrian philosopher with the economists he met at Cambridge and proposes that these may have permeated the philosophical work of Wittgenstein and, in particular, the way in which the anthropological perspective of the philosophical problems, possibly inspired by Gramsci and transmitted by Sraffa, was received and developed by Wittgenstein in his Philosophical Investigations, in the development of concepts such as form of life and language games. It is concluded that Gramsci's theories about hegemony and linguistic alienation bear a certain similarity to Wittgenstein's philosophy of everyday language.